An assessment on the impact of diversification on profitability and growth: a case of Fidelity Life Assurance Company Zimbabwe - Chinyakuza, Epaphras M. (Midlands State University, 2017)
The study was taken to analyze the impact of diversification on the profitability of Fidelity Life Assurance Company. The study covered the period from 2012 to 2015. The researcher reviewed prevailing literature by several authors to identify the research gap on diversification’s impact on profitability of Fidelity Life Assurance Company. The research adopted the case study approach and made use of both primary and secondary data. The target population consisted of Fidelity Life Assurance Company personnel. These included managers, accounts staff and project administrators since these were the ones who were knowledgeable about the area of research. The researcher used random sampling to select the research subjects. Questionnaires and interviews were the key research instruments used to collect data. Questionnaires were delivered in person and appointment date and time was set for the interviews. The collected data was analysed using the Likert scale model and results were presented using pie charts, tables and graphs in a way that allowed rational conclusions to be drawn up. The study revealed that, diversification has a bearing on the company’s core operations. Most of the respondents pointed out that, the strategy had a negative effect on the core operations of Fidelity Life Assurance Company. Challenges that arose as a result of diversification were noted. Major challenges attributed to diversification included administrative difficulties, complexity in coordinating activities, biases in the valuation methods, corporate governance and cross-subsidization effect. The study recommended that Fidelity Life Assurance Company should carry out careful planning and meticulous research as the costs of failure are literally irreversible and detrimental to the company.